Deformation mechanics in inclined, brittle-ductile transpression zones: Insights from 3D finite element modelling. (August 2020) - Nabavi, Seyed Tohid; Alavi, Seyed Ahmad; Díaz-Azpiroz, Manuel; Mohammadi, Soheil; Ghassemi, Mohammad Reza; Fernández, Carlos; Barcos, Leticia; Frehner, Marcel
Abstract: Most natural examples of transpression zones developed at oblique convergence regime are inherently 3D and have inclined boundaries. A 3D finite element model with an elasto-plastic rheology is used to investigate the structural and mechanical evolution of inclined transpression zones in a rock sequence above a frictional basal detachment. Inelastic constitutive relationships allow permanent strains to develop in response to the applied loads. FE-modelling results show that oblique convergence is accommodated by discrete deformation at the main pre-existing inclined faults (=70°) and by distributed brittle and ductile deformation at active blocks. Oblique contraction at the active blocks resulted mainly in layer-parallel shortening, orthogonal to the model outer boundaries, whereas thickening in the horizontal and vertical directions was accommodated via layer-parallel, fault strike-parallel extension and up-dip extrusion (i.e., inclined extrusion). Lateral extrusion should have compensated the rest and/or volume loss took place. Folding and thickening of the mobile backstop produced a non-cylindrical, asymmetric, bi-vergent anticline where permanent strains developed principally in the steep forelimb. Secondary, conjugate fault zones also accommodate oblique slip and contribute to uplift. Displacement vectors within the transpression zone are rotated counter-clockwise (ca. 20°–30°) with respect to vectors in the fixed backstop. Areas with higher rotation values seem to correlate with those showing higher ellipticity values. The presence of pre-existing faults favored strain partitioning from the onset of deformation. FE-modelling results compared with analytical, natural example, and analogue modelling results show that our mechanical modelling can overall match inclined transpression zones geometry that present different modes of strain partitioning and localisation. Highlights: Analytical, kinematical, analogue, and mechanical models are combined to analyse the inclined transpression zone. Transpression zone with oblique convergence angle of 25° results in a pure-shear-dominated, triclinic inclined model with inclined extrusion. FE-modelling results demonstrate oblique convergence at the model was accommodated by discrete deformation at the main pre-existing inclined faults and by distributed brittle-ductile deformation at active blocks. The width of the transpressional zone, the dip of zone boundaries, the angle of oblique convergence, mechanical stratigraphy, amount of oblique convergence, and the presence of tectonic inheritance play important role in strain localisation, the amount of localisation along the transpression zone.